APLIKASI KONVERTER KALIMAT AKTIF-PASIF BERBASIS ANDROID - Asih Pujiastuti; Nurcahyani Dewi Retnowati; Nurwahiddatur Rohman (Compiler, 2017)
Active-Passive Sentences Converter is an android-based application that aims to transform active sentences into passive voice, it’s expected to facitate help elementary school children especially in particular to transform the active-passive sentences. The system on the application does not work if the entered sentences does not meet the S-P-O element, and for the predicate is not the same  as the active verb. If the user has entered the sentence in accordance with the standard active sentence then system will move the object on the active sentence into the subject on the passive sentence as well as the subject becomes the object, and replace the active verb into a passive verb with the particle di- on the predicate. This application can only be operated at least on 4.4 Kitkat android version. The result of the application tested was awesome with the 92% of correct percentage, after applied at three elementary schools are SD Jomblangan, SDN Adisucipto, SDIT Salsabila Al Muthi’in, SDN Berbah 1 and SD Muhammadiyah Noyokerten.